Treatment of periprosthetic femoral fractures after femoral revision using a long stem - Kim, Youngwoo (BMC Musculoskelet Disord, 2015)
BACKGROUND: Periprosthetic femoral fractures are becoming increasingly common and are a major complication of total hip arthroplasty and hemiarthroplasty. The treatment of periprosthetic femoral fracture after femoral revision using a long stem is more complex and challenging. The purpose of this study was to identify the clinical and radiographical features of periprosthetic femoral fractures after revision using a long stem. METHODS: We report a retrospective review of the outcomes of treatment of 11 periprosthetic fractures after femoral revision using a long stem. Eleven female patients with a mean age of 79.2 years (70 to 91) were treated for a Vancouver type B1 fracture between 1998 and 2013. The mean numbers of previous surgeries were 3.1 (2 to 5). RESULTS: The average follow-up was 58.9 months (8 to 180). We found several important features that might influence the outcome of treatment for periprosthetic femoral fractures after femoral revision using a long stem: 1) all cases were classified as Vancouver type B1. 2) 6 patients (55%) had a transverse fracture around the tip of the long stem. 3) 7 patients (64%) had a history of previous fracture of the ipsilateral femur. The type B1 fractures were treated with open reduction and internal fixation in 9 hips, 6 of which were reinforced with bone grafts. Two other periprosthetic fractures were treated with femoral revision. One was revised because of stem breakage, and the other was a transverse fracture associated with poor bone quality, which received a femoral revision with a long stem and a plate. All fractures except one achieved primary union. This failed case had a bone defect at the fracture site, and revision surgery using a cementless long stem and allografts was successful. CONCLUSIONS: These findings suggest that most cases of type B1 fracture after revision using a long stem have been treated successfully with open reduction and internal fixation. However, a transverse fracture with very poor bone quality might be considered as a type B3 fracture, and femoral revision might be a treatment of choice.